Engineered biochar from microwave-assisted catalytic pyrolysis of switchgrass for increasing water-holding capacity and fertility of sandy soil - Mohamed, Badr A.; Ellis, Naoko; Kim, Chang Soo; Bi, Xiaotao; Emam, Ahmed El-raie (Elsevier BV, 2016)
Engineered biochars produced from microwave-assisted catalytic pyrolysis of switchgrass have been evaluated in terms of their ability on improving water holding capacity(WHC), cation exchange capacity (CEC) and fertility of loamy sand soil. The addition of K3PO4, clinoptilolite and/or bentonite as catalysts during the pyrolysis process increased biochar surface area and plant nutrient contents. Adding biochar produced with 10 wt.% K3PO4 + 10 wt.% clinoptilolite as catalysts to the soil at 2 wt% load increased soil WHC by 98% and 57% compared to the treatments without biochar (control) and with 10 wt.% clinoptilolite, respectively. Synergistic effects on increased soil WHC were manifested for biochars produced from combinations of two additives compared to single additive, which may be the result of increased biochar microporosity due to increased microwave heating rate. Biochar produced from microwave catalytic pyrolysis was more efficient in increasing the soil WHC due to its high porosity in comparison with the biochar produced from conventional pyrolysis at the same conditions. The increases in soil CEC varied widely compared to the control soil, ranging from 17 to 220% for the treatments with biochars produced with 10 wt% clinoptilolite at 400 degrees C, and 30 wt% K3PO4 at 300 degrees C, respectively. Strong positive correlations also exist among soil WHC with CEC and biochar micropore area. Biochar from microwave-assisted catalytic pyrolysis appears to be a novel approach for producing biochar with high sorption affinity and high CEC. These catalysts remaining in the biochar product would provide essential nutrients for the growth of bioenergy and food crops. (C) 2016 Elsevier B.V. All rights reserved.